Stress Level Overviews of Final Semester Students in Faculty of Health Universitas Nahdlatul Ulama Surabaya - Rosyadah, Amrina; Firmansyah, Dio; Hardiastuty, Hanny Elok; Fauziah, Khusniada Inayatul; Sunaryo, Merry (Universitas Nahdlatul Ulama Surabaya, 2024)
Stress is a condition that can be caused by uncontrolled physical, environmental, and social demands. Stress can come from external factors originating from the environment or caused by the individual's internal perception. Stress in students can also be caused by stress in the form of parental demands, the complexity of the courses used in the thesis, a bad environment, conflict with friends, meeting supervisors, and other people. This research provides an overview of the stress level in final-semester students at the Faculty of Health, Universitas Nahdlatul Ulama Surabaya. The research design used in this research is pre-experimental The variables used are a quantitative approach that focuses on one variable, namely stress levels. The research results showed that respondents experienced severe stress with a percentage of (71%) and those who experienced mild stress were (29%). This study used five indicators of stress sources including lack of understanding of the topic of 8 students (11%). This economic factor indicator is one of the factors widely experienced by students with a total of 28 students (39%), in comparison concerns about not being able to take the exam 27 students (37%). In addition, two other indicators, namely family and friend support as many as 7 students (10%) and 2 students (3%) came from supervisors. Keywords : Final-semester, student, indicator, stress